A Comprehensive Study on Hydroxyl Multiwalled Carbon Nanotubes Used as Catalysts for VO2+/VO2+ Reaction in Vanadium Redox Flow Battery. (30th November 2019) - Li, Qiang; Bai, Anyu; Qu, Zeqiang; Zhang, Tianyu; Li, Jie; Zhang, Xiaochen; Yu, Mingfu; Xue, Zhichao; Sun, Hong
Abstract : A comprehensive study on the hydroxyl multiwalled carbon nanotubes (hydroxyl MWCNTs) as catalysts in a positive reaction was performed to improve the efficiency of the vanadium redox flow battery (VRFB). The physicochemical properties of the hydroxyl MWCNT-modified electrode were characterized by using a scanning electron microscope (SEM), conductivity measurement, Brunner–Emmet–Teller (BET) measurement, X-ray photoelectron spectroscopy (XPS) analysis, cyclic voltammetry (CV) tests, electrochemical impedance spectroscopy (EIS) analysis, and charge-discharge tests. The prepared composite electrode possesses a huge amount of oxygen-containing groups, high-specific surface area, high electrical conductivity, and high catalytic activity towards the VO2 + /VO 2+ reaction based on physicochemical characterization. The hydroxyl MWCNT-modified graphite felt (hydroxyl MWCNTs/GF) shows the best cell performance with the energy efficiency of 79.74% and remains in high stability after 50 cycles. The improved cell performance is probably ascribed to the increase in active sites, fast charge transfer, and mass transfer rate of the introduced hydroxyl MWCNTs.